A comparative analysis of the characteristics of the water removal processes in preparation for incineration of typical wood waste and forest combustible materials. (15th January 2022) - Kuznetsov, G.V.; Nigay, N.A.; Syrodoy, S.V.; Gutareva, N. Yu; Malyshev, D. Yu
Abstract: The article presents the results of the experimental studies of the processes of removing moisture from fairly typical and widespread forest combustible materials, and woodworking waste under conditions of their thermal preparation for combustion. Based on the results of the experiments, the main regularities of the drying processes of woody biomass under conditions of radiation-convective heating have been established. The integral characteristics (characteristic times) of the drying process of forest biomass under typical (for this technology) heating conditions have been determined. The experiments were carried out on equipment that provides a low level of error (less than 3.3%) for determining the main characteristics of the biomass dehydration process. The values of the mass rates of moisture removal ( W eva ) of four promising (for modern and future power engineering) and fairly common types of biomass have been established in the ambient temperature range from 333 to 393 K, which corresponds to the operating modes of the drying equipment of power plants. According to the results of the experiments, it was shown that at relatively moderate ambient temperatures (333≤ T g ≤ 353 K), the type of wood has a rather significant effect on the characteristics and conditions of the dehumidification process. At the same time, the process of drying wood chips is much faster compared to other types of biomass. As the ambient temperature rises (at 373≤ T g ≤ 393 K), the influence of the type of biomass decreases. As a result of the experiments, a physical model of the process of removing moisture from the bulk layer of biomass was formulated. According to the results of the experiments, it was found that before burning forest biomass in boilers of thermal power plants, it is most advantageous to carry out drying in conditions of relatively moderate (at 333≤ T g ≤ 353 K) ambient temperatures. The studies carried out provide grounds for justifying the use of forest combustible material as fuel (or one of the components of the fuel mixture) at thermal power plants currently operating on coal. Graphical abstract: Image 1 Highlights: Forest fuel is a promising fuel for thermal power plants (TPP). Established two temperature regimes for drying forest biomass. At moderate ambient temperatures, the influence of the type of biomass is significant. Low-temperature drying biomass drying is more efficient than high-temperature drying. The rate of drying of all types of biomass at high temperatures are almost identical.